Effects of Cyperus rotundus extract on spatial memory impairment and neuronal differentiation in rat model of Alzheimer's disease - Zeinab Shakerin; Ebrahim Esfandiari; Shahnaz Razavi; Hojjatallah Alaei; Mustafa Ghanadian; Gholamreza Dashti (Advanced Biomedical Research, 2020)
Background: Alzheimer's disease (AD) is one of the most common neurodegenerative diseases in the older population and characterized by progressive memory and cognitive impairment. Cyperus rotundus, a traditional medicinal herb, has analgesic, sedative, and anti-inflammatory effects and also used to increase memory in Islamic traditional medicine. This study was designed to consider the effects of C. rotundus extract on memory impairment and neurogenesis in the Beta-Amyloid rats' model. Materials and Methods: Forty-two male Wistar rats were randomly divided into six groups (n = 7) for the evaluation of baseline training performance in the Morris water maze test. Then, amyloid-beta (Aβ1-42) was injected in animal hippocampal CA1 bilaterally in four groups. The first probe trial was performed 21 days after Aβ injection. Then, 250, 500, and 750 mg/kg of C. rotundus extract were administered to three Aβ-injected groups for 1 month; after that, the second probe trial was performed, and rats were sacrificed after 28 days of the second probe trial. The neurogenesis was detected in the hippocampus, by immunohistochemical staining. Results: This study showed that spatial memory increased in the behavioral test in AD treated group with C. rotundus extract, compared with the AD group (P = 0.02). Immunohistochemical staining revealed that neuronal differentiation has been occurred in the hippocampus in the AD-treated group with C. rotundus extract compared with the AD group (P = 0.01). Conclusions: This study showed that C. rotundus extract, repaired spatial memory impairment in the Aβ rats, through increased neurogenesis in the hippocampus, which could be related to the flavonoid components in the extract.